The legal problems of foreign investment in developing countries - Nwogugu, E. I. ([Manchester] : Manchester University Press : [New York] : Oceana Publications, 1965)
This book examines the legal aspect of foreign investment in developing states. It contains detailed account and legal analysis of private investment problems and existing arrangements.
Includes index
Includes bibliographical references (p. 296-305).
usc 10/08/18
Loans
Keywords: Investments, Foreign; Investments, Foreign (International law); Developing countries